Women artists in history : from antiquity to the present - Slatkin, Wendy (Prentice Hall, 1997)
This concisely written book introduces readers to the most recent contributions of women to the history of art from the ancient past to the year 2000. It also focuses on the roles of women as patrons and collector along with the ways in which women have been, represented in imaginary in different periods. Organized chronically of western civilizations and the roles women have played in their visual cultures, it highlights contributions from the Middle Ages to the present. Coverage includes Europe from 1450-1800; 19th Century France, United States and Victorian England; the Post World War II Era; contemporary art; and a conclusion of global issues for women artists: past, present, and future.